Injecting immediacy into media logic - Cushion, Stephen (Javnost (Ljubljana), 2014)
This study of UK evening newscasts (1991-2013) interprets the degree to which political news has become mediatised, drawing on the concept of journalistic interventionism to explore edited and live conventions. News examined generally offered little evidence of mediatisation. But when live news was isolated and interpreted over time the study found newscasts were injected with a logic of immediacy, adopting a level of interventionism apparent in instant and rolling news formats. To better understand the mediatisation of politics, future studies could experiment more by theorising different media logics and developing more format specific content indicators that reflect broader influences in journalism.
Keywords: Velika Britanija; mass media; množični mediji; novinarstvo; journalism; informiranje; obveščanje; politics; politika